Fertilizer Requirements and Nutrient Dynamics of Teak (Tectona Grandis L.F.) Plantations in Peninsular Malaysia - Siddiqui, Muhammad Tahir (1998)
Teak (Tectona grandis L.f) is one of the highly sought after timbers of the world. It is not indigenous to Malaysia and was introduced as plantation species in the northern states of Kedah and Perlis in early 1950's. To-date, 1100 ha of teak plantation has been established in Malaysia and more acreage are planned in the future. However, comprehensive fertilizer requirements of this species are not adequately known. The objective of the present study was to determine the fertilizer requirements of T grandis and their effects on the nutrient dynamics in the trees. Three experiments were conducted for this purpose: pot trial, field trial and destructive sampling of various aged trees. Soil and plant analyses were carried out to determine the effects of fertilizer application and age on the nutrient concentrations in the trees. Results of the pot trial revealed that 564 kg/ha of ammonium sulphate and 3 00 kg/ha of P205 with 75 kg/ha of K20 promoted the growth of T grandis' seedlings. The results of field experiment clearly indicated that N and P are equally important and act additively to boost the growth of teak seedlings. It was found that 200 kg/ha ammonium sulphate and 300 kg/ha triple superphosphate gave maximum height and diameter of the teak seedlings. The disparity in fertilizer dosages is due to large number of plants per ha in pot experiment.